2016
DOI: 10.1377/hlthaff.2015.1379
|View full text |Cite
|
Sign up to set email alerts
|

Prices For Common Medical Services Vary Substantially Among The Commercially Insured

Abstract: Using a national multipayer commercial claims database containing allowed amounts, we examined variations in the prices for 242 common medical services in forty-one states and the District of Columbia. Ratios of average state prices to national prices ranged from a low of 0.79 in Florida to a high of 2.64 in Alaska. Two- to threefold variations in prices were identified within some states and Metropolitan Statistical Areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…16 The data include the amount paid by the insurer plus any copayments or other payments made by the patient. 17 We also compared to Medicaid physician reimbursement rates publicly reported by the Texas Medicaid program based on new office visit CPT codes 99203-99205 for orthopedic surgeons. 18 Analysis For all calls, we calculated the relative risk that patients with Medicaid or who were uninsured would receive an appointment compared with privately insured patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The data include the amount paid by the insurer plus any copayments or other payments made by the patient. 17 We also compared to Medicaid physician reimbursement rates publicly reported by the Texas Medicaid program based on new office visit CPT codes 99203-99205 for orthopedic surgeons. 18 Analysis For all calls, we calculated the relative risk that patients with Medicaid or who were uninsured would receive an appointment compared with privately insured patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, healthcare costs in Texas are generally near or slightly below national averages. 17 Dallas in particular has the highest costs of any metropolitan area in Texas for knee replacements, which may indicate that its costs for orthopedic care are higher than average. 17 Texas also has the highest uninsured rate in the nation, which may exacerbate access difficulties and health disparities in this state.…”
Section: Limitationsmentioning
confidence: 99%
“…Goz and colleagues recently found significant regional differences in the cost for spinal surgery across the United States. Newman and colleagues found that, despite the differences expected based on operation costs in different regions, the variability in price appears to be largely a result of market dynamics in a given area. As they indicated, additional research is now required to understand the market dynamics and determine why there is such great variation across the country for the same services and whether this variation is justifiable.…”
Section: Discussionmentioning
confidence: 99%
“…Our results contribute to the growing literature in health economics on price dispersion for medical supplies (Grennan & Swanson, 2018;Grennan, 2013), pharmaceuticals (Starc & Swanson, 2018), and medical services (Cooper, Craig, Gaynor, & Van Reenen, 2018;Newman, Parente, Barrette, & Kennedy, 2016;Xu, et al, 2015;Dunn, Liebman, & Shapiro, 2017). 3 The previous papers looking at medical services have relied on data sets that do not include explicit information on the payer with which each patient is associated.…”
Section: New Contributionmentioning
confidence: 68%